2021
DOI: 10.1111/nph.17887
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of masting: economies of scale are not reduced by negative density‐dependence in seedling survival in Sorbus aucuparia

Abstract: Masting is a widespread reproductive strategy in plants that helps to reduce seed predation and increase pollination. However, masting can involve costs, notably negative densitydependent (NDD) seedling survival caused by concentrating reproduction in intermittent events. Masting benefits have received widespread attention, but the costs are understudied, which precludes understanding why some plant species have evolved intense masting, while others reproduce regularly.We followed seed production, seed predati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 72 publications
(119 reference statements)
1
19
0
Order By: Relevance
“…We showed that temporal variation in the abundance of new recruits and total rainfall significantly affects seedling vital rates, and that these effects are mediated by changes in the strength of biotic interactions. Our findings are in accordance with the Economy of Scale hypothesis, mainly reported at the seed-to-seedling stage and rarely investigated at the seedling stage after their emergence (but see Hett, 1971;Huang et al, 2021;Seget et al, 2021). We further showed that years of higher recruitment experience reduced seedling growth, likely because of increased competition for resources.…”
Section: Con Clus Ionssupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that temporal variation in the abundance of new recruits and total rainfall significantly affects seedling vital rates, and that these effects are mediated by changes in the strength of biotic interactions. Our findings are in accordance with the Economy of Scale hypothesis, mainly reported at the seed-to-seedling stage and rarely investigated at the seedling stage after their emergence (but see Hett, 1971;Huang et al, 2021;Seget et al, 2021). We further showed that years of higher recruitment experience reduced seedling growth, likely because of increased competition for resources.…”
Section: Con Clus Ionssupporting
confidence: 92%
“…In addition, years of higher seed production might produce seeds with higher seed mass and nutrient reserves due to greater pollination efficiency, thus increasing seedling survival (Sork, 1993). Whether the predictions of the Economy of Scale hypothesis hold true after the germination phase has been rarely tested (Hett, 1971; Huang et al, 2021; Seget et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is likely a simplification. Even generalist predators suffer population crashes when seed crops fluctuate ( 8 , 14 , 15 ), and even specialist predators are susceptible to satiation during mast years ( 30 , 58 , 59 ). Furthermore, masting plants can be synchronized over hundreds or even thousands of kilometers ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…80%–90% to c . 20%–30% (Bogdziewicz et al, 2021; Seget, Bogdziewicz, Holeksa, Ledwoń, Milne‐Rostkowska, et al, 2022; Żywiec et al, 2013). In the light of this past evidence, we believe that the higher proportion of fruits recruited under rowan trees after mast years was a result of starvation of seed predators.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, insect predation exerts a selection pressure towards masting by promoting more synchronised tree phenotypes (Bogdziewicz et al, 2021). Finally, an analysis of costs (elevated density‐dependent seedling mortality following pulsed recruitment) and benefits of masting indicated that masting improves fitness in rowan (Seget, Bogdziewicz, Holeksa, Ledwoń, Milne‐Rostkowska, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%